The Role of Sustainable Financial Policies in Strengthening the Innovation Ecosystem and Commercialization of Knowledge-Based Ideas within the National Economy (Scientific Journal of Research Studies in Future Management, 2025)
In recent decades, sustainable fiscal strategies have gained increasing attention as essential levers for reinforcing innovation ecosystems and advancing knowledge-driven economic structures. These frameworks seek to achieve harmony between economic expansion, fiscal stability, and systematic support for innovation, thereby laying the groundwork for sustainable progress. The present study, using a descriptive–analytical methodology, investigates the influence of sustainable financial policies on the commercialization of knowledge-based initiatives within Iran’s national economic context. Empirical data were compiled from reliable international and domestic institutions, including the World Bank, the OECD, and Iran’s Vice-Presidency for Science and Technology. The results suggest that employing sustainable fiscal instruments—such as green financing mechanisms, innovation-centered tax incentives, and long-term R&D investments—contributes meaningfully to improving innovation performance and enhancing the competitiveness of knowledge-based enterprises. Furthermore, the establishment of transparent and adaptive fiscal frameworks that integrate innovation impact assessments is of paramount importance. Overall, sustainable fiscal policy emerges not merely as a means of economic regulation but as a principal catalyst for innovation vitality and the long-term development of knowledge-oriented economies.